Improving Students’ Learning Outcomes of Islamic Religious Education Sunject Through the Application of Simulation Learning Methods at SMP Negeri 12 Poleang Barat - Nursiah, Nursiah (Journal of Teaching and Education, 2023)
This study aims to find out how the application of the simulation learning method in Islamic Religious Education lessons for students at SMP Negeri 12 Poleang Barat; What are the learning outcomes of Islamic Religious Education for students at SMP Negeri 12 Poleang Barat; and how to increase the learning outcomes of Islamic religious education through the application of simulation learning methods for students at SMP Negeri 12 Poleang Barat. To answer this question, Classroom Action Research (CAR) was conducted which consisted of two cycles with three meetings and one evaluation. While research procedures include planning, implementing observation and evaluation, and reflection. The results showed that in cycle I only 36 out of 42 students met the Maximum Completeness Criteria (KKM), the average score was 70.00, or was in the low category. whereas in cycle II out of 440 of 42 students have met the Maximum Completeness Criteria (KKM) with an average value of 90.00 or are in the high category.Â